2013
DOI: 10.1186/1916-0216-42-53
|View full text |Cite
|
Sign up to set email alerts
|

Molecular predictors of locoregional and distant metastases in oropharyngeal squamous cell carcinoma

Abstract: BackgroundThe incidence of oropharyngeal squamous cell carcinoma (OPSCC) is increasing due to fundamental changes in oncogenesis related to effects of the human papilomavirus (HPV). Virally-mediated tumours behave and respond to treatment differently than their classic, carcinogenically-mediated counterparts despite similar stage and grade of disease. This difference in behaviour has lead to investigation of etiologies of OPSCC at the molecular level.Molecular biomarkers offer potential insight into the behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Multivariate analyses were performed with a Cox regression hazard model. 13,14 Differences between groups were calculated using the t test for continuous variables and the χ 2 test for categorical variables. P < .05 was used to indicate statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analyses were performed with a Cox regression hazard model. 13,14 Differences between groups were calculated using the t test for continuous variables and the χ 2 test for categorical variables. P < .05 was used to indicate statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, overall survival was also found to be poorer in Ki67-positive head and neck SCCs compared with Ki67-negative tumours in two studies, 12,21 although others reported no significant difference in time to recurrence or recurrence-free survival by Ki67 status. 23,24 While previous studies have reported the prognostic significance of HPV and Ki67 as biomarkers in oropharyngeal cancers separately, only one other study has examined these in conjunction. In a retrospective, singleinstitutional study of 56 OSCC cases, Ritta et al reported a favourable outcome in the HPV-positive/Ki67-negative subgroup, with the survival benefit amounting to 2.5-fold relative mortality reduction at 5 years compared with HPV-negative/Ki67-positive patients (although survival graphs for this interaction were not reported).…”
Section: Discussionmentioning
confidence: 99%
“…7,8 This is particularly true for Ki67, where arbitrary cut-offs of 20, 25, 40 %, or using median values as a cut-off for positivity, have been utilized [12][13][14]21,24 compared with the 50 % cut-off used in the current study. There needs to be consensus on the definition of Ki67 positivity in order for the findings of different studies to be compared.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue microarrays (TMAs) were constructed with formalin‐fixed paraffin‐embedded (FFPE) tumor tissue blocks from either pretreatment biopsies or primary surgical specimen, as recently described . A head and neck pathologist (L.P.) reviewed the blocks and excluded cases with inadequate tissue.…”
Section: Methodsmentioning
confidence: 99%